Albumin nanoparticles loaded with the antitumor drug «Hydroxycarbamide» by the incorporation method - Tazhbayev, Ye.M.; Burkeyev, M.Zh.; Zhaparova, L.Zh.; Zhumagaliyeva, T.S.; Agdarbek, A.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In this article the possibility of loading the antitumor drug «Hydroxycarbamide» into the polymeric matrix of human serum albumin was studied. Nanoparticles of serum albumin were obtained using desolvation method. Prepared empty human serum albumin nanoparticles have average size of 108.4 nm with narrow particle size distribution, which make them promising in using for the drug delivery purposes. The binding of hydroxycarbamide with the polymer was performed by incorporation of the drug into the medium during the process of crosslinking of albumin macromolecules. Incorporation of the drug into human serum albumin led to the formation of nanoparticles loaded with hydroxycarbamide with satisfactory physico-chemical characteristics (average particle diameters were in the range of 250–350 nm and the value of polydispersity index was 0.2–0.3) with the high value of binding degree (up to 68 %). It was shown that increasing the concentration of the drug in the initial solution led to the increase of binding degree of hydroxycarbamide with human serum albumin nanoparticles. The kinetics of release process of the drug from albumin nanoparticles in the conditions modeling biological medium was studied. As a result of the study of the drug release rate it has been concluded that prolonged release of hydroxycarbamide can be achieved when nanosomal form of the drug is used.
Қатерлі ісікке қарсы «Гидроксикарбамид» препаратымен енгізу əдісімен иммобилденген альбуминді нанобөлшектер
Наночастицы альбумина, иммобилизованные противоопухолевым препаратом «Гидроксикарбамид» методом включения
Keywords: nanoparticles; human serum albumin; desolvation; antitumor drug; Hydroxycarbamide; incorporation; loading; drug delivery; polymers